1999
DOI: 10.1038/sj.bjc.6690441
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of rck/p54, a DEAD box protein, in human colorectal tumours

Abstract: SummaryThe RCK gene is a target of the t(11;14)(q23;q32) chromosomal translocation observed in human B-cell lymphoma, and the overexpression of its protein (rck/p54) by the translocation was shown to cause malignant transformation. The rck/p54 protein belongs to the DEAD box protein/RNA helicase family, which has a variety of functions such as translation initiation, pre-mRNA splicing and ribosome assembly. The expression of rck p54 in colorectal adenocarcinoma cells was examined by immunohistochemistry and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 8 publications
4
65
1
Order By: Relevance
“…Similarly, other DEAD box RNA helicases appear to be involved in tumor development. For instance, Rck/p54 is overexpressed in neuroblastoma, glioblastoma, rhabdomyosarcoma and lung cancer cells as well as in colorectal tumors (Akao et al, 1995;Nakagawa et al, 1999). Further, the DDX1 RNA helicase gene is often coamplified with N-myc in retinoblastomas and neuroblastomas and its co-amplification correlates with a poorer prognosis (Godbout and Squire, 1993;Squire et al, 1995;George et al, 1996).…”
mentioning
confidence: 99%
“…Similarly, other DEAD box RNA helicases appear to be involved in tumor development. For instance, Rck/p54 is overexpressed in neuroblastoma, glioblastoma, rhabdomyosarcoma and lung cancer cells as well as in colorectal tumors (Akao et al, 1995;Nakagawa et al, 1999). Further, the DDX1 RNA helicase gene is often coamplified with N-myc in retinoblastomas and neuroblastomas and its co-amplification correlates with a poorer prognosis (Godbout and Squire, 1993;Squire et al, 1995;George et al, 1996).…”
mentioning
confidence: 99%
“…So far, we have consistently reported data showing that high expression of rck/p54, a human DEAD-box/RNA unwindase, is associated with malignant transformation, especially by contributing to enhancement of potentiality for carcinogenesis by the deregulation of translation initiation control (12,14,(17)(18)(19)25). In the present study, we demonstrated that rck/p54 plays a role in the maintenance of cell growth probably by modulating the expression of genes involved in cell proliferation at the translation-initiation step, which is in line with the facts that rck/p54 has been verified as an RNA unwindase (14), its homologues have been reported to be associated with translational control (15,24,25) and, in the current study, rck/ p54 interacted with eIF4E.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that rck/p54 was highly expressed in the majority of malignant cell lines and human colorectal tumors and HCV-related hepatocellular tumors (12,17,18). Also, high expression of rck/p54 frequently accompanied the c-myc overexpression seen in colon tumor cells; and evidence was obtained by the use of rck/p54-overexpressing SW480 cells, supporting the contribution of rck/p54 to the stabilization of c-myc mRNA and efficiency of c-myc translation (19).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with their essential biological roles, inactivation of helicases has been implicated in human genetic disorders such as xeroderma pigmentosum (Weeda et al, 1990), trichothiodystrophy (Broughton et al, 1994), Bloom syndrome (Ellis et al, 1995), Werner syndrome (Yu et al, 1996), and Rothmund Thomson syndrome (Kitao et al, 1999). On the other hand, over-expression of rck/ p54, a protein belonging to the DEAD box protein/ RNA family of helicases, is seen in B-cell lymphomas with t(11 ; 14)(q23 ; q32), and also in 50% of colorectal adenocarcinomas (Seto et al, 1995;Nakagawa et al, 1999). In addition, the DEAD box gene DDX1, encoding a putative RNA helicase, is co-amplified with N-myc in some retinoblastomas and neuroblastomas (Godbout et al, 1998).…”
Section: Introductionmentioning
confidence: 99%